Corpo-realidad : arte, tecnología y lo aparentemente invisible - López, Marta López (2019)
Corpo-reality is a performance of the Spanish creator Maria Castellanos Vicente. In it three key themes of her doctoral thesis converge: the study of perception (the human eye versus its machining version), sensory deprivation of human beings and the relation body-skin. Her wereable, transparent to infrared cameras, shows that artistic creation is research itself